Microstructure evolution and mechanical properties of rheocast A319 aluminum alloy using cooling slope - Salleh, Mohd Shukor; Omar, Mohd Zaidi; Syarif, Junaidi; Mohammed, Mohammed Naser; Alhawari, Khalid Salim (Trans Tech Publications, 2014)
A319 aluminum alloys are commonly used in automotive industry due to a combination of good fluidity and mechanical strength. In this present work, cooling slope (CS) rheocasting process was employed to produce A319 billets with near spherical morphology of primary Al phase. The dendritic primary phase in the cast A319 alloy had readily transformed into nondendritic when the ingots were cast over a cooling plate from pouring temperatures between 620°C and 640°C and with cooling lengths of between 300 mm and 400 mm. The shear driven flow of the solidifying melt on the cooling slope wall promotes heterogeneous nucleation of α-Al phase and subsequent separation from there due to shear driven flow of the solidifying melt produced nearly spheroidal morphology of the primary phase in the microstructure. The results show that the best combination of pouring temperature and cooling length was found to be 630°C and 400 mm respectively. The hardness of the rheocast ingots improved to 85.3 HV from 81.8 HV in as-cast condition.